Pendidikan Moderasi Beragama dan Simbol Keagamaan (Pembentukan Identitas Islam Moderat Anak Melalui Songkok NU Perspektif Teori Konstruksi Sosial Peter Berger) - Abu Muslim; Wilis Werdiningsih (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2023)
This paper examines managing religious moderation education by strengthening religious symbols, namely songkok, with NU logic. This study aimed to analyze how the use of symbols on the NU skullcap can shape the personality of SD Islamiyah Magetan students in forming an understanding of religious moderation from the perspective of Peter L. Berger's social construction theory. How can symbols convey messages about religious moderation as a form of planting moderate Islam and identity formation? This symbol has several functions, such as describing something as well as a form of conveying an implied message. Therefore, to analyze it using the social construction theory approach of Peter L. Berger. From the results of the reading, it can be concluded: First, the implementation of the regulation on wearing the NU songkok at SD Islamiyah Mageran is outlined in a regulation that enforces every male student to wear the NU songkok. Second, Sonkok NU can become an identity and have moderate Islamic values ??found in the relationship between moderate Islamic values ??of NU ideas such as tawasuth, tawazun, tasamuh, and ta’adul, which have an impact on their use in everyday life. Third, Religious Moderation Education through Sonkok NU as a moderate Islamic identity from the perspective of Peter L Berger's sociological theory of knowledge is through a process of externalization, objectivation, and internalization.